Mpox (monkeypox): a comprehensive updated of current epidemic evidence - Amir Hossain; Md. Abdul Monem; Mamunur Rahman; Rashadur Raza (Science in One Health)
Mpox, formerly referred to as monkeypox, is a viral disease endemic to central Africa, resulting from the monkeypox virus (MPXV). This study provides a current overview of the Mpox epidemic as of 2024, emphasizing significant developments and epidemiological trends. The World Health Organization (WHO) initially designated a clade Ⅱb outbreak as a global health emergency in May 2022, which was subsequently managed through vaccination and public health interventions by May 2023. In September 2023, a resurgence of cladeⅠ in the Democratic Republic of the Congo (DRC) resulted in a 160 % increase in cases by 2024. The WHO declared this increase a public health emergency of international concern (PHEIC) in August 2024. The outbreak timeline indicates substantial rises in cases and fatalities, especially among children under 15 in the DRC. Regional analysis reveals that the European Region initially recorded the highest incidence of cases and fatalities. In contrast, regions including African Region (AFRO), Eastern Mediterranean Region (EMRO), South-East Asia Region (SEARO), and Western Pacific Region (WPRO) exhibited a rise in cases, indicating a potential spread or resurgence of the health event. Gender disparities in transmission pathways were apparent, with males exhibiting higher case numbers, particularly via person-to-person contact. The research highlights the necessity of ongoing surveillance, global collaboration, and focused public health measures. The discourse addresses obstacles in vaccine distribution and the necessity for emergency use authorizations, highlighting the imperativeness for adaptive strategies in public health management. This extensive update offers critical insights into the present condition of the Mpox epidemic and the necessary measures to mitigate its proliferation.